PENGARUH METODE FIELD TRIP TERHADAP HASIL BELAJAR DITINJAU DARI SIKAP PEDULI LINGKUNGAN PADA MATERI SUMBER DAYA ALAM KELAS XI IPS SMAN 1 SIANTAN - Nunung Juniarti; Mohammad Gamal Rindarjono; Peduk Rintayati (Universitas Sebelas Maret (UNS), 2017)
The purposes of this research are to know: (1) To determine differences in student learning outcomes in material resources between students and teaching methods for a field trip with students who use the lecture method, (2) To determine the influence of a caring attitude environment students both high and low the learning outcomes in the matter of natural resources, (3) To understand the interaction between the learning method field trip and a caring attitude to the environment students student learning outcomes in natural resource materials. This research used experimental method with 2 x 2 design factor. This research was conducted in August 2016 with student of Junior High School in Siantan as the population. The sampling technique used is Cluster Random Sampling. The sample taken are 68 students consisting of 34 students of class XI IPS 2 as the experiment class and 34 students of class XI IPS 5 as the control class. The data is collected by means of the questionnaires to obtain the students’ attitude data, and class test is used to get the students’ learning outcome. The validity of the instrument is tested by using point validity technique and by using the pearson product moment. Instrument realibility is tested by using Alpha Cronbach. The data analysis technique used is the two-way Variance Analysis with 5% of significance level. The results of this research show that: (1) Method of learning field trip yield the same learning with the learning method lecture in the presentation of material natural resources in class XI IPS SMAN 1 Siantan, (2) attitude is environmentally students on the classification of high using field trip better than the lecture method in influencing student learning outcomes, (3) There is no interaction between the method of field trip and environmentally conscious attitude toward student learning outcomes in natural resource materials on student class XI IPS SMAN 1 Siantan. Keywords: Field Trip Method, Results Learning, Environmental Attitude